PENINGKATAN KEMANDIRIAN MEMAKAI SEPATU BERTALI MELALUI TEKNIK FORWARD CHAINING UNTUK SISWA DISABILITAS INTELEKTUAL RINGAN(CLASSROOM ACTION RESEARCH KELAS VII DI SLB C MUZDALIFAH MEDAN SUMATERA UTARA) - Hartaty Hartaty; Safaruddin Safaruddin; Nurhastuti Nurhastuti; Syari Yuliana (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: Independence in wearing lace-up shoes is an essential self-care skill for students with mild intellectual disabilities, yet it requires fine motor coordination, attention, and sequential understanding that often become learning barriers. This study aimed to improve the independence of seventh-grade students with mild intellectual disabilities in wearing lace-up shoes through the forward chaining technique at SLB C Muzdalifah Medan. Methods: The study used classroom action research conducted in two cycles, with three meetings in each cycle. The participants were four students, namely NAP, HH, RM, and ARP. Data were collected through observation, performance tests, interviews, and documentation, then analyzed descriptively using qualitative notes and quantitative percentages. Results: The students’ independence increased across cycles. At the end of Cycle I, NAP reached 33.33%, HH 50%, RM 66.66%, and ARP 50%, so none met the 70% mastery criterion. After repeated practice, positive reinforcement, and gradual prompt fading in Cycle II, NAP and ARP reached 83.33%, while HH and RM reached 100%. Novelty: The study demonstrates a structured application of forward chaining for lace-up shoe skills in mild intellectual disability learning.